The H19/let-7 double-negative feedback loop contributes to glucose metabolism in muscle cells - Gao, Yuan; Wu, Fuju; Zhou, Jichun; Yan, Lei; Jurczak, Michael J.; Lee, Hui-Young; Yang, Lihua; Mueller, Martin; Zhou, Xiao-Bo; Dandolo, Luisa; Szendroedi, Julia; Roden, Michael; et al. (Nucleic acids research, 2014)
The H19 lncRNA has been implicated in development and growth control and is associated with human genetic disorders and cancer. Acting as a molecular sponge, H19 inhibits microRNA (miRNA) let-7. Here we report that H19 is significantly decreased in muscle of human subjects with type-2 diabetes and insulin resistant rodents. This decrease leads to increased bioavailability of let-7, causing diminished expression of let-7 targets, which is recapitulated in vitro where H19 depletion results in impaired insulin signaling and decreased glucose uptake. Furthermore, acute hyperinsulinemia downregulates H19, a phenomenon that occurs through PI3K/AKT-dependent phosphorylation of the miRNA processing factor KSRP, which promotes biogenesis of let-7 and its mediated H19 destabilization. Our results reveal a previously undescribed double-negative feedback loop between sponge lncRNA and target miRNA that contributes to glucose regulation in muscle cells.